Intervention by Clinical pharmacists in Cardiovascular Disease Management: Evidence from Intervention Studies - Bash, Hala Saad (American Journal of Biomedicine and Pharmacy, 2026)
Cardiovascular diseases (CVDs) represent a range of chronic disorders impacting blood vessels and heart, contributing to the reduction of the quality of life and contributing significantly to increased rate of mortality as well as morbidity. Clinical pharmacists contribute as integral members of the healthcare team concerning treatment of chronic diseases, involving cardiovascular conditions. This review aims to present the responsibility of clinical pharmacists in the treatment of patients diagnosed with cardiovascular diseases. This review was performed as a structured narrative review. Several studies published in Google Scholar, PubMed, and Science Direct which issued between 2012 and 2024 were reviewed. The review summarizes evidence on clinical outcomes, including blood pressure and glycemic control, lipid profile outcomes, medication adherence, and economic impact. By integrating findings across diverse healthcare settings, existing evidence suggests that the active participation of clinical pharmacists may be associated with an improvements in patients counseling, risk factors control, medication safety, medication adherence, and a reduction in hospitalization and medication costs.